Welfare Effects of Public Procurement of Medicines: Evidence from Ecuador - Callejas, Jerónimo; Mohapatra, Debi Prasad (International Journal of Industrial Organization, 2021)
Abstract: This article evaluates the welfare implications of a public procurement program, where the Ecuadorian government procures medicines used for cancer treatment and distributes it to patients for free with the aim to benefit the poor. Using a unique dataset on Ecuador’s pharmaceutical market, we estimate a structural model of demand and supply, and focus on two research questions related to this program. First, we consider a targeting strategy commonly implemented in various developing countries, where patients below a given income threshold qualify for the free drug. We compare this with a simpler drug distribution mechanism where every patient is a potential recipient of the free drug and the patients are served on first-come-first-serve basis. Our results show that the poor patients do self-select into the program, and the first-come-first-serve strategy does benefit the poor more compared to the relatively rich. However, the targeting strategy does a much better job in serving the poorest patients. Second, we study the supply side implications of this program. Our counterfactual exercises show that when the government procures low-cost drugs and provides them for free, it distorts the supply side incentives, and hence, market prices of similar low-cost drugs may increase by about 7% in response. Prices of the high cost drugs remain mostly unaffected. Therefore, the policy may end up negatively affecting near-poor patients that did not qualify for the free government drug.
Code: International Journal of Industrial Organization
Keywords: Business history in Latin America